The Outflow Ranking Method for Weighted Directed Graphs - René van den Brink; Robert P. Gilles (Tinbergen Institute, 2006)
A ranking method assigns to every weighted directed graph a (weak) orderingof the nodes. In this paper we axiomatize the ranking method that ranksthe nodes according to their outflow using four independent axioms. This outflowranking method generalizes the ranking by outdegree for directed graphs.Furthermore, we compare our axioms with other axioms discussed in the literature.
Keywords: C65; D71; 330; Decision analysis; Weighted directed graph; Ranking method